Corporate Ownership Structure, Sustainability Culture, and Corporate Financial Reporting Quality: A Literature Review - Kurniawan, Putu Sukma; Asri Savitri, Ni Luh (Universitas Gorontalo, 2025)
In the contemporary business landscape, the issue of sustainability has emerged as a pivotal concern for corporate management. The crux of this issue lies in the alignment of a company's business operations with the interests of the social community and environmental sustainability. The integration of the SDGs concept into business activities is poised to become a fundamental element of corporate culture. This phenomenon is inextricably linked to the company's ownership structure and the quality of its financial reporting. This study employs a literature review (LR) research design to examine patterns of previous research in the context of corporate ownership structure, sustainability culture, and the quality of corporate financial reporting as well as to provide suggestions for future research in this research area. LR's research design, which is based on an online literature search platform, has the capacity to identify research trends within the context of corporate ownership, sustainability culture, and financial reporting quality. The findings of the research indicate that these three subjects continue to be of interest for further study. A number of recommendations for future research topics have been formulated on the basis of the study's findings. For instance, there is a need to focus on corporate ownership structure and the implementation of sustainability culture.